IMPLEMENTATION OF MIND MAPPING-BASED DISCOVERY LEARNING MODEL IN ONLINE LEARNING ON COLLOID MATERIALS - Mahdian Mahdian; Rilia Iriani; Leny Leny; Rinda Oktavia Novianti (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2024)
Research has been conducted on the implementation of the discovery learning model based on mind mapping in online learning on colloid materials. This study aims to determine the difference in knowledge learning outcomes, attitudes, and student responses to the discovery learning model based on mind mapping in online learning on colloid materials. The method used is a quasi-experiment using a "non-equivalent control group design" design. The research sample was students of class XI MIA 1 as the experimental class and class XI MIA 2 as the control class at MAN 2 Tabalong. Data collection used test and non-test techniques. Data analysis techniques used descriptive analysis and inferential analysis. The results showed (1) there was a significant difference in knowledge learning outcomes between the experimental class and the control class where the t-value > t-table (α = 0.05) with an average value for the experimental class of 86.67 with an average N-gain value of 0.74, while for the control class it was 77.56 with an average N-gain value of 0.60, (2) the attitudes of students' learning outcomes had different average values where in the experimental class it was 78.59 higher than the control class which was 72.30, (3) student responses to the discovery learning model based on mind mapping in online learning on colloid materials were in the good category.